2022
DOI: 10.1001/jamapsychiatry.2021.2669
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pain Reprocessing Therapy vs Placebo and Usual Care for Patients With Chronic Back Pain

Abstract: IMPORTANCE Chronic back pain (CBP) is a leading cause of disability, and treatment is often ineffective. Approximately 85% of cases are primary CBP, for which peripheral etiology cannot be identified, and maintenance factors include fear, avoidance, and beliefs that pain indicates injury.OBJECTIVE To test whether a psychological treatment (pain reprocessing therapy [PRT]) aiming to shift patients' beliefs about the causes and threat value of pain provides substantial and durable pain relief from primary CBP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
127
2
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(140 citation statements)
references
References 79 publications
6
127
2
5
Order By: Relevance
“…The effect sizes were generally small, but above the cut-off value for clinical relevance ( Table 2 ) [ 54 , 55 ]. These results are generally consistent with those from studies conducted in other cultural settings [ 56 , 57 ]. In fact, the small size of the effect on disability triggered by education is in line with most medical treatments for LBP [ 6 , 7 , 58 ]…”
Section: Discussionsupporting
confidence: 91%
“…The effect sizes were generally small, but above the cut-off value for clinical relevance ( Table 2 ) [ 54 , 55 ]. These results are generally consistent with those from studies conducted in other cultural settings [ 56 , 57 ]. In fact, the small size of the effect on disability triggered by education is in line with most medical treatments for LBP [ 6 , 7 , 58 ]…”
Section: Discussionsupporting
confidence: 91%
“…This research 3 along with another randomized controlled study 27 demonstrated interventions that not only reduced but in many cases cured chronic pain by retraining the brain. Techniques for retraining the brain away from chronic pain include psychological therapies, 1 , 25 , 28 , 29 , 33 , 38 , 42 , 46 , 47 , 51 , 57 , 62 , 68 70 , 88 , 89 , 97 education, 61 , 64 , 67 , 79 , 85 biofeedback, 31 , 76 , 80 activities, 2 , 17 , 44 , 54 , 55 , 63 , 87 , 91 , 92 , 96 and meditation.…”
Section: Introductionmentioning
confidence: 81%
“…In particular, functional magnetic resonance imaging (fMRI) has been used to demonstrate changes in the brain that are consistent with chronic pain. 3 6 , 12 , 13 , 24 , 34 , 53 , 56 , 74 , 77 , 83 One recent randomized controlled study 3 found significant changes in fMRI of subjects with chronic back pain before and after psychological pain treatment, showing a possibility of using fMRI in pain measurement. However, fMRI is rather expensive and hard to do for routine use.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the variability of behavioral responses and fostering explorative behavior may be a valuable treatment target in patients with chronic pain. 45 Behavioral treatments targeting operant-learning mechanisms are available, 46,47 and Ashar et al 48 showed that brain connectivity patterns may predict successful cognitive-behavioral treatment of CBP. Moreover, the transition from subacute to CBP was prevented in patients treated with Levodopa combined with naproxen and was associated with a normalization of altered vmPFC-NAc connectivity specifically in female patients with SABP, while naproxen alone did not have beneficial effects.…”
Section: Discussionmentioning
confidence: 99%